2013
DOI: 10.1111/j.1548-2456.2013.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Presidential Preferences? The Supreme Federal Tribunal Nominations in Democratic Brazil

Abstract: This article studies the processes of nomination and appointment to the Supreme Federal Tribunal in Brazil made by Presidents Sarney through Lula da Silva. It shows that in relations with the Senate, presidential anticipation prevails over presidential dominance. Brazilian presidents are successful appointers because they invest great effort in the moment of selection, when potential candidates are tested in the juridical and political communities. As a consequence, a uniform Senate approval of candidates coex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Liberal and conservative judges have been shown to diverge significantly in their decision making behaviour (Epstein et al., 2013; Martin and Quinn, 2002; Segal and Spaeth, 2002). Studies of judicial bodies in Europe and elsewhere have produced similar findings (Hangartner et al., 2015; Hanretty, 2012; Hönnige, 2009; Llanos and Lemos, 2013; Voeten, 2007).…”
Section: Related Workmentioning
confidence: 62%
See 1 more Smart Citation
“…Liberal and conservative judges have been shown to diverge significantly in their decision making behaviour (Epstein et al., 2013; Martin and Quinn, 2002; Segal and Spaeth, 2002). Studies of judicial bodies in Europe and elsewhere have produced similar findings (Hangartner et al., 2015; Hanretty, 2012; Hönnige, 2009; Llanos and Lemos, 2013; Voeten, 2007).…”
Section: Related Workmentioning
confidence: 62%
“…While studies conducted in various contexts have found evidence for the impact of ideology (Alarie and Green, 2009; Hanretty, 2012, 2013; Llanos and Lemos, 2013; Voeten, 2007; Weiden, 2011), the few that have undertaken to assess the effect of policy preferences on the rulings of EU judges present serious limitations. Due to the unavailability of the judges’ voting record, scholars have resorted to proxies, such as the party manifesto score of the appointing government (Frankenreiter, 2017; Malecki, 2012) or the legal tradition of the sitting judge (Zhang et al., 2018), whose validity is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Due to institutional arrangements, justices in civil law jurisdictions are simply insulated from political interests (Pasquino, 1998;Ferejohn and Pasquino, 2004). For instance, the mechanism of appointment in Brazil has been perceived as consensual and depoliticized by some scholars (Llanos and Lemos, 2013). Other legal scholars argue that the role of the legal professions and a strong sense of judicial independence have eliminated any causal relationship between presidential interests and judicial behavior (Ribeiro, 2011).…”
Section: The Hypothesismentioning
confidence: 98%
“…Empirical debate about other constitutional courts is an emerging literature (see, among others, Alarie and Green, 2008;Garcia et al, 2009;Franck, 2009Franck, , 2010Garoupa et al, 2013;Green and Alarie, 2009;Sala, 2009;Tate and Sittiwong, 1989;Vanberg, 2005;Volcansek, 2000). More importantly, the particular case of the Brazilian Supreme Court has been studied by relatively fewer scholars and empirical work based on regression analysis is not common yet (notable exceptions being Jaloretto and Mueller, 2011;Llanos and Lemos, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…4 As peculiaridades da nossa forma de organização política, especialmente a complexidade do sistema de indicação dos ministros do STF, dificultaram significativamente a utilização dos modelos dos EUA acerca das posições ideológicas dos juízes, que tendem a categorizar as ideologias judiciais por meio de modelos em que sempre há dois polos, representados pelas posições defendidas por Democratas e Republicanos. Os desafios não pararam aí: além de um sistema partidário mais fragmentado, o que dificulta o mapeamento ideológico das indicações de magistrados com base na proxy das indicações presidenciais (Llanos & Lemos, 2013), o imenso volume de decisões do STF (vide Hartmann & Chada, 2015) compromete sua comensurabilidade em relação a tribunais como a Suprema Corte norte-americana.…”
Section: Introductionunclassified